Qualidade do leite de cabra produzido no Semi-Árido do Rio Grande do Norte - Mendes, Carolina de Gouveia (Universidade Federal Rural do Semi-Árido, 2009)
This study evaluated the quality of raw goat milk produced in the Semi-Arid Region of Rio Grande do Norte. Twenty herds were monitored for October/2008 to February/2009. Where ten herds were of the city of Mossoró and ten herds of the city of Apodi. To assess the quality, the samples from each herd underwent physical tests - chemical (density, fat, total solids, solids-not-fat contents, protein, lactose, pH and conductivity) through ultrasound equipment (total EKOMILK ®) and microbiological (bacteria mesophiles -- Log CFU / mL, total coliforms and thermotolerant - Log MPN / mL). The work was conducted in two stages, the first samples were collected from milk producers without guidance on Good Agricultural Practice (GAP), and collected in the municipality of Mossoró 40 samples (four replicates) and the city of Apodi 30 samples were collected ( three replicates), the collections were made in the dry season. Before the second stage talks were held to clarify the application of Good Agricultural Practice. In the second phase were collected during the rainy season the city of 19 samples Mossoró (four replicates) in the city of Apodi were evaluated 30 samples (three replicates), totaling 119 samples of milk. Through the medium of general physico-chemical analysis, it was observed that all tests were within the standards set by legislation, but observing the absolute values, some samples showed density in disagreement with the law. The count of mesophilic bacteria remained within the standards. The microbiological tests worsened during the rainy season. The care and milking animal health should be intensified during rainy months
Keywords: Caprinos leiteiros; Boas práticas agropecuárias; Análises físico-químicas; Microbiológica; Dairy goats; Good agricultural practices; Physical-chemical analysis; Microbiological; CIENCIAS AGRARIAS::MEDICINA VETERINARIA